the Role Of Health Media In Crisis Management-corona Pandemic As - ح نان مجاهد (International Journal of Social Communication, 2021)
Health media is a form of specialized information. Through audio, visual, written and even electronic means, it attempts to disseminate health culture and to raise awareness of medical and health concepts and behaviors. Through this article, we will try to uncover the role and importance of health media in managing the crisis of the Corona Covid Virus 19 outbreak that has engulfed the world